Quantum interference spectroscopy with rubidium - Schultz, Eric M. (Kansas State University, 2010)
A recent powerful spectroscopic technique that has been implemented using femtosecond lasers excites atoms or molecules through quantum interference effects. The results are oscillations in excited state populations that represent the optical frequencies used in the excitation pathway, these frequencies can be found by Fourier analysis. The technique uses a Mach-Zender interferometer wherein one femtosecond pulse is split into two pulses that are phase coherent. These pulses are the pump and probe pulses which are delayed with respect to one another by a variable time. During the delay between pulses the state excited by the first (pump) pulse evolves in time before the probe pulse is used to excite the atom into its final state. The observed final state population exhibits interference between the several possible pathways to the final state. The information gained from this method will allow for advances in other processes such as the dynamics of photo-association.
Keywords: spectroscopy; rubidium; interferometer; Physics, Atomic (0748)